Security framework of cloud data storage based on multi agent system architecture - a pilot study. - Mohamed Talib, Amir; Atan, Rodziah; Abdullah, Rusli; Azmi Murad, Masrah Azrifah (2012)
Cloud computing environment is required an efficiency security techniques due it's contains a numbered of assets such as data, users, technologies, resources and business transactions. Multi Agent system (MAS) architecture is critical to ensure high security facilitation based on the way of its development. A security framework based on MAS architecture to facilitate confidentiality, correctness assurance, availability and integrity of collaborative cloud data storage (CDS) environment is proposed. In order to verify our proposed security framework based on MAS architecture, a pilot study is conducted using a questionnaire survey. Rasch software is used to analyze the pilot data. Item reliability is found to be poor and a few respondents and items are identified as misfits with distorted measurements. As a result, some problematic questions are revised and some predictably easy questions are excluded from the questionnaire.